T-plastin expression downstream to the calcineurin/NFAT pathway is involved in keratinocyte migration. - Cécilia Brun (Public Library of Science (PLoS), 2014)
Cutaneous wound healing requires keratinocyte proliferation, migration and differentiation to restore the barrier function of the skin. The calcineurin/nuclear factor of activated-T-cell (NFAT) signaling pathway has been recently shown to be involved in keratinocyte growth, differentiation and migration. It is induced by an increased intracellular calcium rate and its inhibition results in decreased capacities of keratinocytes to migrate. Nevertheless, the link between calcineurin activation and keratinocyte migration remains unknown. Recently, Orai1, a pore subunit of a store-operated calcium channel that favors calcium influx, was shown to play a critical role to control proliferation and migration of basal keratinocytes. Of interest, the actin-bundling T-plastin is crucial in cell motility through cross-linking to actin filament and its synthesis was shown to be induced by calcium influx and regulated by the calcineurin/NFAT pathway in tumor Sezary cells. We investigated herein the role of the calcineurin/NFAT pathway-dependent T-plastin in keratinocyte migration, by quantifying T-plastin expression in keratinocytes and by analyzing their migration under calcineurin inhibition or knockdown of NFAT2 or T-plastin. We did confirm the role of the calcineurin/NFAT pathway in keratinocyte migration as shown by their decreased capacities to migrate after FK506 treatment or siNFAT2 transfection in both scratching and Boyden assays. The expression of NFAT2 and T-plastin in keratinocytes was decreased under FK506 treatment, suggesting that T-plastin plays a role in keratinocyte migration downstream to the calcineurin/NFAT pathway. Accordingly, siRNA knockdown of T-plastin expression also decreased their migration capacities. Actin lamellipodia formation as well as FAK and β6-integrin expression were also significantly decreased after treatment with FK506 or siRNA, reinforcing that NFAT2-dependent T-plastin expression plays a role in keratinocyte migration. These results indicate that T-plastin might be considered as a major actor in the mechanisms underlying calcineurin/NFAT-dependent keratinocyte migration and may explain wound-healing defects observed in patients under calcineurin inhibitor long-term treatment.